2017
DOI: 10.3390/nu9101048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Involvement of IL-9 and IL-22 in Cows’ Milk Allergy in Infants

Abstract: Although allergic inflammation is characterized by a T helper (Th) 2-dominant immune response, the discovery of a role for new T cell subsets in inflammatory diseases has added an additional layer of complexity to the understanding of the pathogeneses of allergic diseases. We evaluated plasma cytokine profiles in infants with cows’ milk allergy (CMA), who were being treated with an elimination diet. In a prospective, randomized and controlled study, infants (aged 8.4 ± 3.9 months) with CMA were treated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
14
0
6
Order By: Relevance
“…43 Apart from the association with peanut allergy, a role for IL-9 secreting cells is also suggested in cow's milk allergy, since a study in cow's milk allergic children showed a correlation between IL-9 plasma levels and eosinophilia, which is known to contribute to allergy development. 44 Combined, these results stress the importance of Th9 cells in allergic pathologies and underline their potential as target for future allergy treatment, although further investigation is clearly needed.…”
Section: Diseasesmentioning
confidence: 75%
See 1 more Smart Citation
“…43 Apart from the association with peanut allergy, a role for IL-9 secreting cells is also suggested in cow's milk allergy, since a study in cow's milk allergic children showed a correlation between IL-9 plasma levels and eosinophilia, which is known to contribute to allergy development. 44 Combined, these results stress the importance of Th9 cells in allergic pathologies and underline their potential as target for future allergy treatment, although further investigation is clearly needed.…”
Section: Diseasesmentioning
confidence: 75%
“…Moreover, this study clearly characterized these IL‐9 secreting cells as Th9 cells and showed even a discriminatory Th9 response between peanut‐allergic and peanut‐sensitized children . Apart from the association with peanut allergy, a role for IL‐9 secreting cells is also suggested in cow's milk allergy, since a study in cow's milk allergic children showed a correlation between IL‐9 plasma levels and eosinophilia, which is known to contribute to allergy development …”
Section: Th9 Cells In Allergic Diseasesmentioning
confidence: 99%
“…Increased levels of IL‐4 and IL‐13 and decreased levels of IL‐9, IL‐17A, and IFNy were recorded in children with cow's milk allergy compared with healthy controls. After 120 days of elimination diet, these patients had a decrease in IL‐4, IL‐9, IL‐13 and IL‐22, and an increase in IL‐17A …”
Section: Discussionmentioning
confidence: 96%
“…Barros et al reports that infants with cow's milk protein allergy had a higher plasma IL-4 and IL-13 concentrations, which were significantly lower after the elimination diet. 33 Experimental animal models, investigating intestinal allergic sensitization process reveal, that following allergen encounter, intestinal epithelial basement membrane was disrupted and an increased influx of immune cells, including neutrophils, was observed. 34 According to our data children with AD had significantly higher FC, compared to healthy controls (36.5 mg/kg vs. 6.45 mg/kg, p=0.018).…”
Section: Discussionmentioning
confidence: 99%